Wearable Technologies - Düking, P.; Sperlich, B. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
Wearables are miniaturized devices worn close to the body that record various physical, chemical, or biological signals. These recorded signals are analyzed as parameters, interpreted, and feedbacked to the user. It is important to acknowledge that not all parameters are reliably and validly collected. However, thanks to technological developments, more and more parameters can be reliably and validly collected in various application scenarios. Wearables allow to aggregate and combine different data from the training procedure and everyday life. Through the collected data, dose-response relationships between training and physiological adaptation can be better investigated and understood. With proper use and data interpretation, wearables can be beneficial in informing training processes (e.g., to improve endurance performance parameters).